A Political Display and Symbolic Reasoning of Budgeting: Organizational Control Systems in An Indonesian Higher Education Institution - IMAM WAHYUDI (The Indonesian Journal of Accounting Research, 2013)
This study examines the impact of the paternalistic managerial style of Javanese culture in an Indonesian higher education institution on the role budgeting used within the organization. This is an ethnographic case study in which the researcher is part of the case being studied as an academic and administrative staff member. An historical analysis is performed by confirmation of other organizational participants' understanding about the school's control system through interviews. To provide official organizational and descriptive historical contexts of the case and to make available the powerful link between what people say and what they actually do, documents and archival recordsare also used. Instead of formal organizational structures being adopted, informal relationships, paternalistic management and physical control dominate everyday managerial practices in the school. Budgeting facilitates a political deal among the school's stakeholders. It functions as a rationalized myth to the process and a symbolic reason to display that managerial conducts are financially responsible - not merely an efficiency measurement.